Does Angiotensin‐Converting Enzyme Inhibitor and β‐Blocker Use Reduce the Risk of Primary Liver Cancer? A Case–Control Study Using the UK Clinical Practice Research Datalink. Issue 2 (5th February 2016) - Hagberg, Katrina Wilcox; Sahasrabuddhe, Vikrant V.; McGlynn, Katherine A.; Jick, Susan S.
Abstract : Study Objective: It has been suggested that use of the antihypertensive drugs angiotensin‐converting enzyme (ACE) inhibitors and β‐blockers may decrease the risk of primary liver cancer; thus, the objective of this study was to evaluate whether use of ACE inhibitors and/or β‐blockers is associated with a lower risk of liver cancer. Design: Nested case–control study. Data Source: United Kingdom Clinical Practice Research Datalink. Patients: We identified 490 cases with hypertension and a first‐time (incident) diagnosis of primary liver cancer between 1988 and 2011. To account for an induction period, the index date was defined as the date of the first recorded liver cancer diagnosis minus 1 year. Controls were selected from patients with hypertension in the CPRD during the study period with a recorded diagnosis of hypertension who had no diagnosis of liver cancer and were free of any other cancer (except nonmelanoma skin cancer) before the index date; they were matched up to a 4:1 ratio to cases based on index date (same index date as that of their matched case), age (same year of birth), sex, general practice, and number of years of recorded history in the CPRD before the index date (1909 controls). Both cases and controls were required to have at least 2 years of recorded activity in the database before the index date. Measurements and Main Results: Exposure was defined as receipt of two or more prescriptions for ACE inhibitors and/or β‐blockers before the index date; the reference group was nonuse (0–1 prescription) of ACE or β‐blocker prescriptions before the index date. We also examined the effect of duration of use and, separately, the effect of individual drugs within each medication class on risk of liver cancer, and conducted analyses restricted to patients without liver disease or diabetes mellitus. Conditional logistic regression analysis was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). No association was found between use of ACE inhibitors and/or β‐blockers and the risk of liver cancer compared with nonuse (adjusted OR 1.14, 95% CI 0.85–1.55). No significant differences were noted in risk by duration of use or by individual drugs, or after restricting the analyses to patients without diabetes or liver disease. Conclusion: Use of ACE inhibitors and/or β‐blockers was not associated with reduced risk of primary liver cancer compared with nonuse of these drugs in persons with hypertension.